Regions' Size and Regional Competitiveness in the 4th EU Programming Period, 2007-2013. Regional Units in Greece - George Mihailidis; Giorgos Georgiadis; Nikos Koutsomarkos (European Regional Science Association (ERSA), 2006)
(This paper is the result of a research program that was carried out by the Laboratory for Evaluation of Development Policies and Programs, University of Thessaly, for the Greek Ministry of Economics and National Economy). Does size matter? Is regional competitiveness affected by the regions size? Are regional problems in Greece the same or differentiated among regions? Could an administrative reform create better development preconditions? The designation of the 13 Regions in the 80s in Greece basically stemmed from the need to create development units for programming and managing the development planning. Nonetheless, the designation of regions under the effect of historical factors and political expediency led to uneven area as well as population sizes. Moreover, up to today, Greece has put its major developmental effort in the infrastructures sector, while the new 4th programming period 2007-2013 imposes competitiveness objectives and an integration of the Lisbon Strategy in the Coherence policy that constitute an innovation for the Greek reality. Thus, the question occurs whether the Greek Regions are capable to formulate and implement corresponding strategies and programmes. This paper discusses the performance of the 13 Greek regions against other comparable EU regions and presents indexes reflecting the relative progress of the Greek regions, through critical review of statistical data concerning development level and regional competitiveness. At the same time the paper considers how a restructure of resources, competences, and geographical boundaries will enable: i. Concentration of managerial effort ii. Better control of programme implementation. iii. Better utilization of the limited available personnel . iv. More economical use of equipment and facilities. And finally programme operation monitoring at the regional level through the formation of larger and more powerful regional entities, vis-vis the central Administration. To this purpose administrative decentralization schemes of various EU Countries are reviewed. The paper proposes a restructuring as follows: All the competences concerning decision-making and management of the programming are concentrated to Regional Unions. The Regions retain only proposal functions, as centers of local bodies consensus and local initiatives' mobilization. The paper also elaborates on a generalized administrative scheme for the Unions and the Regions. Summing up the discussion highlights the necessity to form larger and more powerful regional units in Greece, where ones strategic disadvantages will be compensated by the advantages of the other and through them many local economies altogether will build a scale capable to integrate their productive structure, to cause the emergence of new functions and to constitute their negotiatory advantage for FDI and activities attraction.
Keywords: 330